Crafting Sonic Worlds: Developing a Comprehensive Curriculum for Sound Design - Igor Karaca (Journal of the Association for Technology in Music Instruction, 2025)
In this paper presentation we will explore effective pedagogical strategies for engaging college students in the field of sound design. The presentation will outline a comprehensive curriculum that balances theoretical knowledge with hands-on experience, emphasizing the importance of creativity and collaboration.